HPC@Cloud: A Provider-Agnostic Software Framework for Enabling HPC in Public Cloud Platforms - Munhoz, Vanderlei; Castro, Márcio (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2022: Anais do XXIII Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/wscad.2022.226528, 2022)
The cloud computing paradigm democratized compute infrastructure access to millions of resource-strained organizations, applying economics of scale to massively reduce infrastructure costs. In the High Performance Computing (HPC) context, the benefits of using public cloud resources make it an attractive alternative to expensive on-premises clusters, however there are several challenges and limitations. In this paper, we present HPC@Cloud: a provideragnostic software framework that comprises a set of key software tools to assist in the migration, test and execution of HPC applications in public clouds. HPC@Cloud allows the HPC community to benefit from readily available public cloud resources with minimum efforts and features an empirical approach for estimating cloud infrastructure costs for HPC workloads. We also provide an experimental analysis of HPC@Cloud on two public clouds: Amazon AWS and Vultr Cloud.